Normal and Reverse Flow Injection Analysis Methods for Estimation of Mesalazine in Pharmaceutical Dosage Forms - hasan, Bayan; Hadi, Hind (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Determining the actual amounts of active ingredients in various pharmaceutical commercial forms is still receiving a lot of attention. Two flow injection analysis (FIA) methods were suggested for determination of mesalazine (MES) in pharmaceutical forms. Normal and reverse FIA systems (nFIA and rFIA) combined with UV-Vis spectrophotometric technique were used for the analysis. The methods involved using two mods of FIA systems for measuring a colored product result from coupling of MES with 2,2’-dihydroxybiphenyl after oxidized with sodium periodate in alkaline medium. The absorbance of the red colored dye was measured at maximum wavelength of 500 nm. The calibration graphs for MES were linear in the ranges 2.5-200 and 0.5-60 µg/mL with RSD of best than 3% for both methods respectively. Also the limits of detection were 1.2 and 0.2 µg/mL and limits of quantitation were 3.6 and 0.7 µg/mL of MSL for nFIA and rFIA systems respectively. All physical and chemical conditions of flow systems such as flow rate, reaction coil length and reagent concentrations were carefully studied. The proposed methods were applied for determining MES in four commercial tablets without any interferences.